CAD/CAM – MANUFACTURE OF ORTHOPEDIC STRUCTURES - Khojimuradov Burkhan Ravshanovich (Sciental Journals Publishing, 2025)
Imagine that in one step you make an impression, simulate a restoration and install a crown for the patient. Fiction? No, this is the same CAD/CAM system — Computer Assisted Design/Computer Aided Manufacturing or a system for computer modeling and manufacturing dentures.